Comparison of systemic and epidural xylazine and ketamine anaesthesia for external skeletal fixation in cattle - Kinjavdekar, P; ., Amarpau; Aithal, H P; Hoque, M; Maiti, S K; Singh, G R (The Indian Journal of Animal Sciences, 2011)
Systemic and epidural xylazine (0.1 mg/kg and 0.05 mg/kg) and ketamine (till effect and 100 mg/kg) were evaluated for fixation of either linear or circular external fixator in tibial or radial or metatarsal osteotomies in crossbred cattle. Our results indicated that the anaesthesia produced by both techniques was ofgood quality, depth and duration. However, general anaesthesia produced better muscle relaxation, analgesia and sedation required for fixation ofexternal skeletal fixator for immobilization ofradial, tibial and metatarsal osteotomies as compared to epidural analgesia. The technique ofgeneral anaesthesia with xylazine (0.1 mg/kg) and ketamine till effect may be used as a preferred method for induction and maintenance ofanaesthesia as compared to epidural use ofthese drugs.Â